A review of the built-environment attributes for Qur’anic memorization process - Ab Jalil, Nurlelawati; Awang, Arita Hanim; Salleh, Nurul Hamiruddin; Ab. Jalil, Habibah; Salim, Siti Suria (Kulliyah of Architecture & Environmental Design, International Islamic University Malaysia, 2018)
A conducive learning environment not only could promote positive learning behaviour and improve students’ well-being, but also reinforce the better learning process and institutional objectives. The purpose of this study is to investigate activity patterns of Quran memorization and Quranic studies through analysis of 22 major local Tahfiz centres. This article highlights on method and findings of a significant parameter in designing a learning environment for the Tahfiz students. It reviews the multitude of perspectives on the Tahfiz ecosystem that has an influence on the Tahfiz centre operation, the memorization method, behaviour and other requirements in the education of a Hafiz. The paper concludes with significant key findings based on the reviews and connection to the existing theories from the mainstream educational research for the guidance of further investigation.